Thermodynamic Study on the Adsorption of Pb2+ and Zn2+ From Aqueous Solution by Human Hair - A. S. Ekop; N. O. Eddy (E-Journal of Chemistry)
Adsorption of Pb(II) and Zn(II) ions from aqueous solutions was studied in a batch system using modified human hair. The optimum conditions for the adsorption of Pb(II) and Zn(II) ions from aqueous solution by human hair were investigated by considering the extent of adsorption with respect to contact time, initial metal ion concentration and temperature. The results obtained indicates that the extent of metal ions removed decreases with increasing contact time but increased with increase in the initial metal ion concentration. The adsorption equilibrium data best fitted Freundlich adsorption isotherm. The adsorption of Pb(II) and Zn(II) ions onto human hair is endothermic, spontaneous and is characterised by increasing degree of orderliness.